Determinants of Employee Change Readiness: A Study of Transformational Leadership and Self-Efficacy and the Role of Organizational Commitment - Rahmat Runa (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2023)
The covid pandemic requires the readiness of employees to deal with the work system. This study aims to determine the effect of Transformational Leadership, Self-Efficacy, and Organizational Commitment on Readiness to Change and to determine the role of Organizational Commitment in mediating the relationship between Transformational Leadership and Self-Efficacy on Readiness to Change. This study was conducted at the Civil Servants of the Regional Secretariat of Poso Regency with a population of 260 people. The sample in this study used a purposive sampling technique of 118 respondents. The exogenous variables in this study are Transformational Leadership and Self-Efficacy, while the endogenous variables are Readiness to Change mediated by Organizational Commitment. Variable measurements were carried out using a Likert scale. Data analysis was performed using the Structural Equation Model (SEM) with the PLS (Partial Least Square) approach. The software used for structural analysis uses Smart PLS 3.2.9. The results of the analysis show that Transformational Leadership and Self-Efficacy have a positive and significant effect on Organizational Commitment. Transformational Leadership, Self-Efficacy, and Organizational Commitment have a positive and significant impact on Readiness to Change. Organizational Commitment partially mediates the relationship between Transformational Leadership and Self-Efficacy and Readiness to Change.